Proteomic analysis of the salt-responsive leaf and root proteins in the anticancer plant Andrographis paniculata Nees - Talei, Daryush; Valdiani, Alireza; Yusop, Mohd Rafii; Mahmood, Maziah (Public Library of Science, 2014)
Separation of proteins based on the physicochemical properties with different molecular weight and isoelectric points would be more accurate. In the current research, the 45-day-old seedlings were treated with 0 (control) and 12 dS m−1 of sodium chloride in the hydroponic system. After 15 days of salt exposure, the total protein of the fresh leaves and roots was extracted and analyzed using two-dimensional electrophoresis system (2-DE). The analysis led to the detection of 32 induced proteins (19 proteins in leaf and 13 proteins in the root) as well as 12 upregulated proteins (four proteins in leaf and eight proteins in the root) in the salt-treated plants. Of the 44 detected proteins, 12 were sequenced, and three of them matched with superoxide dismutase, ascorbate peroxidase and ribulose-1, 5-bisphosphate oxygenase whereas the rest remained unknown. The three known proteins associate with plants response to environmental stresses and could represent the general stress proteins in the present study too. In addition, the proteomic feedback of different accessions of A. paniculata to salt stress can potentially be used to breed salt-tolerant varieties of the herb.